SOSIALISASI PENTINGNYA TOLERANSI TERHADAP PERBEDAAN PENDAPAT DI DESA SIMOREJO KEPOHBARU BOJONEGORO - Laila Tri Lestari; Domingos Ferreira; Faiza Qurotul Aini (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2020)
Community service activities carried out by the Islamic University Community Service Program at the University of Darul Ulum Lamongan which was held in early July 17 to 17 August 2019. That is Located in the village of Simorejo, Kepohbaru sub-district, Bojonegoro district, it has made a very significant contribution for the community members, especially in the Simorejo village area, Kepohbaru sub-district, Bojonegoro district, received very good reception and high enthusiasm. The socialization of the importance of tolerance towards differences of opinion carried out in Kepohbaru District can be used as a first step to prevent unfair behavior and improve unsafe environmental conditions as well, and to prevent the risk of social jealousy that can result in division among villages. As of late there has been a lack of familiarity between villages, which has resulted in the prosperity of the village. Some of the factors supporting these activities include: the socialization participants have a great willingness to obtain information and knowledge about the importance of maintaining friendship between people, knowing the importance of mutual cooperation and social. And how to communicate well with others. Some of the obstacles faced at the time of socialization were the importance of being tolerant of differences of opinion among people. (1) There are limitations in supporting facilities for conducting socialization and presentations, including the absence of a projector LCD. (2) Training activities planned to run for 2 days could not be realized due to collision with the activities of the participants who were mostly farmers, where their activities began in the morning. So the socialization team found it difficult to adjust the suitable time.